Pengaruh Penghindaran Pajak (Tax Avoidance) Pada Nilai Perusahaan dengan Transparansi Sebagai Variabel Pemoderasi - Juliartha Nugraha, Made Caesar; Ery Setiawan, Putu (E-Jurnal Akuntansi, 2019)
Tax is a compulsory contribution to the state owed by an individual or entity that is a force based on the Law by not getting compensation directly and used for state needs for the greatest prosperity of the people. The purpose of this study was to determine the effect of tax avoidance (tax avoidance) on company value with transparency as a moderating variable. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2014-2016. The number of samples used in this study were 60 companies with the number of observations 180 obtained by non-probability sampling techniques with purposive sampling method. Data analysis techniques were carried out using moderated regression analysis. The results of the research conducted show that tax avoidance (tax avoidance) has a positive effect on firm value. The study also found that transparency was able to moderate the effect of tax avoidance on firm value. Keywords: Tax Avoidance, Transparency, Corporate Value